Football psychology : from theory to practice - Konter, Erkut; Beckmann, Jürgen; Loughead, Todd (Abingdon, Oxon ; New York, NY : Routledge, 2019)
Presenting an empirically underpinned synthesis of research and theory, while offering guidance for applied practitioners, this is the first book to comprehensively map the psychology of learning, playing, and coaching the world's favourite sport. The book provides a complete analysis of key topics that capture the broad range of football psychology such as personality, motivation, cognition, and emotion; coaching and team essentials; psychological skills for performance enhancement; and developing players in youth football. Including contributions from a range of international researchers, each chapter provides a review of the relevant literature, key theories, real-world examples, and reflections on how knowledge can be applied in practice. Split into four sections, the book covers a diverse range of topics relevant not only to coaching and performance but also to personality development and health promotion. Essential reading for any student, researcher, or professional in the area, the book is the most cutting-edge overview of how psychology can explain and improve the way football is both played and understood.
Number of training hours -- Self-regulatory skills and their development -- Examples of self-regulatory skill use in professional football -- The use of self-regulatory skills for the attainment of professional football -- Determining attained performance level -- How is the ECI determined? -- Method and analyses -- Results of our analyses -- Self-regulatory learning or just doing more outside training -- An example of reflective thinking in practice -- Limitations and future research perspectives -- Men's versus women's football -- Conclusions and practical implications -- References -- 23 Helping players develop life skills in football -- Abstract -- Understanding positive youth and life skills development -- Research on life skills -- Developing life skills through football -- Implications for guiding practice -- Conclusions -- References -- 24 The critical transition from junior to elite football: resources and barriers -- Abstract -- Holistic view of the transition to being a professional player -- The transition to professional football on the field -- The transition to professional football off the field -- Academic level and dual careers -- Conclusions and practical implications -- References -- 25 Preventing depression and burnout in youth football -- Abstract -- Theory and research -- Practical implications -- Future research directions and conclusions for applied sport psychologists active within football -- Conclusion -- References -- Index.
Includes bibliographical references and index.
Print version record.
Erkut Konter has various degrees specializing in Sport Psychology and Football. He has more than 30 years' experience as a sport psychology consultant and football coach at national and international levels. He has a number of publications on football psychology and is currently at the Dokuz Eylèul University, çIzmir, Turkey. Jèurgen Beckmann is Professor and Chair of Sport Psychology at Technical University of Munich, Germany and Honorary Professor of the University of Queensland, Australia. He is a former president of the German Association of Sport Psychology. He has been consultant to numerous elite athletes and teams since 1987 including professional football teams of the German Bundesliga. Todd M.Loughead, PhD, is Professor of Sport and Exercise Psychology in the Department of Kinesiology and Co-Director of the Sport Psychology and Physical Activity Research Collaborativeat the University of Windsor, Canada. His current research interests are related primarily to group dynamics including athlete leadership, coaching, cohesion, and team-building. Outside of work, he enjoys coaching bothfootball and ice hockey.
eBooks on EBSCOhost
Keywords: Soccer -- Psychological aspects; GAMES -- Gambling -- Sports; SPORTS & RECREATION -- Business Aspects; SPORTS & RECREATION -- Essays; SPORTS & RECREATION -- History; SPORTS & RECREATION -- Reference; TRAVEL -- Special Interest -- Sports; PSYCHOLOGY -- General; PSYCHOLOGY -- Applied Psychology; Soccer -- Psychological aspects